Fatty acid binding protein-4 is associated with disability in multiple sclerosis patients - Bove, Riley; Healy, Brain C; Musallam, Alexander; Soltany, Pejvak; Diaz-Cruz, Camilo; Sattarnezhad, Neda; Glanz, Bonnie I; Kivisäkk, Pia; Miller, Karen K; Chitnis, Tanuja (Multiple sclerosis, 2019)
Increased adiposity is a risk factor for multiple sclerosis (MS) and is associated with increased disability scores. Adipokines may mediate the effects of adiposity on MS disease course. The objective of this study is to examine the association between the adipokines (leptin and fatty acid binding protein-4, FABP4) and clinical course in individuals with MS. Subjects (18-65 years) with relapsing-remitting MS or clinically isolated syndrome and <10 year disease duration were selected from a longitudinal clinical study. Cross-sectional and longitudinal models assessed the relationship between two adipokines (leptin and FABP4) and disease severity in women and men, adjusting for age, disease duration and disease type, Vitamin D level, testosterone level, and as well by body mass index (BMI). Mean age of subjects ( N = 163, 56% women) was 39.3 years. Higher FABP4 levels were associated with higher Expanded Disability Status Scale (EDSS) scores in women in both univariate and multivariate analyses (odds ratio: 1.30; p = 0.005). In men, higher FABP4 level was significantly associated with change in EDSS over time (estimate: 0.0062; p = 0.035). We found no association of FABP4 levels with time to next relapse or a measure of processing speed. FABP4 levels may be associated with increased disability in both men and women with MS independent of effects of BMI and other hormones. Future studies should expand these analyses and further explore downstream mechanisms of adiposity-related effects in MS.